Exploring the interplay of product quality and service attributes in consumer purchase decisions: Insights from sustainable business practices - Rizqi Saputra, Muhammad; Efriyani Sumastuti; Violinda, Qristin (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Understanding the factors that influence customer purchase decisions is essential in the competitive culinary industry. This study aims to examine the interplay between product quality and service attributes, alongside location, menu variation, and price, in shaping customer behavior at Takashimura Kudus, a local culinary business. Previous studies have highlighted the importance of these factors individually, but their combined effects remain underexplored. Methods: The study employed a quantitative research design, using purposive sampling to collect data from 100 respondents. A structured questionnaire measured consumer perceptions of key variables using a Likert scale. Data were analyzed using multiple linear regression to identify both individual and collective influences of the factors on purchase decisions. Findings: Results indicate that menu variation is the only variable with a positive and significant individual effect on purchase decisions, while location, product quality, service quality, and price do not show significant individual effects. However, these factors collectively influence purchase decisions significantly. This suggests that businesses must adopt a comprehensive strategy that integrates these elements to meet consumer expectations effectively. Conclusion: The study highlights the critical role of menu diversity as a driver of consumer behavior and the need for businesses to address multiple factors simultaneously to remain competitive. Novelty/Originality of Article: This research provides a novel perspective by analyzing the combined effects of product quality, service attributes, and other factors, emphasizing their collective significance in the context of small-scale culinary enterprises.